Respuesta :

i believe the answer is y= -3

Answer:

Step-by-step explanation:

Did you mean  (y+4)^2 = 2?  " ^ " denotes exponentiation.

Expanding (y+4)^2 = 2, we get y^2 + 8y + 16 = 2, or

y^2 + 8y + 14 = 0

Let's apply the quadratic formula.  First, find the discriminant, b^2 - 4ac:

8^2 - 4(1)(14) = 64 - 56 = 8 (which is the square of 2√2).

Because the discriminant is positive, there are two real, unequal roots (solutions).  They are:

      -8 ± √8

x = -------------- = -4 ± √2

           2